2010
DOI: 10.1016/j.ydbio.2009.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of oral siphon pigment organs in the ascidian Ciona intestinalis

Abstract: Ascidians have powerful capacities for regeneration but the underlying mechanisms are poorly understood. Here we examine oral siphon regeneration in the solitary ascidian Ciona intestinalis. Following amputation, the oral siphon rapidly reforms oral pigment organs (OPO) at its distal margin prior to slower regeneration of proximal siphon parts. The early stages of oral siphon reformation include cell proliferation and re-growth of the siphon nerves, although the neural complex (adult brain and associated organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(146 citation statements)
references
References 44 publications
5
141
0
Order By: Relevance
“…This variability actually reflects the constraints applied by both the developmental status of the organism and the pre-injury homeostatic conditions of the injured tissue on this module. Indeed the length of this module is directly influenced by the intensity of the developmental and aging processes on-going in the regenerating organism 84,85 : basically no need for a bridge between wound healing and re-development in the embryo, but a bridge that gets longer with the closing of the developmental processes and the progressive appearance of aging in the adult. Also the homeostatic status at the time and place of injury defines which cellular tools can be activated upon injury.…”
Section: How Many Routes To Launch a Regenerative Process?mentioning
confidence: 99%
“…This variability actually reflects the constraints applied by both the developmental status of the organism and the pre-injury homeostatic conditions of the injured tissue on this module. Indeed the length of this module is directly influenced by the intensity of the developmental and aging processes on-going in the regenerating organism 84,85 : basically no need for a bridge between wound healing and re-development in the embryo, but a bridge that gets longer with the closing of the developmental processes and the progressive appearance of aging in the adult. Also the homeostatic status at the time and place of injury defines which cellular tools can be activated upon injury.…”
Section: How Many Routes To Launch a Regenerative Process?mentioning
confidence: 99%
“…Subsequently, a detailed analysis showed that the NC could be completely replaced within about a month after ablation (Schultze, 1899). Many different investigators have now confirmed NC and oral siphon regeneration and contributed additional details about the processes (Sutton, 1953;Whittaker, 1975;Bollner et al 1992Bollner et al , 1993Bollner et al , 1995Bollner et al , 1997Dahlberg et al, 2009;Auger et al, 2010). The capacity for complete regeneration from body fragments has also been investigated.…”
Section: Partial Body Regenerationmentioning
confidence: 98%
“…Recent studies of Ciona regeneration have focused on the oral siphon as a model (Auger et al, 2010;Jeffery, 2012;. The oral siphon is a thin muscular tube covered by tunic on its outer side ( Fig.…”
Section: The Oral Siphon Modelmentioning
confidence: 99%
See 2 more Smart Citations